Relationship between Emotion Regulation and Grit in High School Athlete Students: Hubungan antara Regulasi Emosi dengan Grit pada Siswa Atlet di Sekolah Menengah Atas - Agustina, Nurul Aini; Widyastuti, Widyastuti (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the relationship between emotional regulation variables and grit variables in athletes at SMA Negeri Sport East Java. The type of research used is quantitative correlation with the independent variable of emotion regulation and the dependent variable grit. This study involved all student athletes from class X – XII, totaling 210 student athletes. The sampling technique used is saturated sampling, in which all the population is sampled. Data collection in this study used the emotion regulation scale adopted from Ginting (2018) and the grit scale adopted from Oktaviasari (2021) with a Likert scale model. Based on the results of the correlation test of 0.102, it was stated that there was no relationship between emotional regulation and grit with a significance value of 0.141 > 0.005. The results showed that the emotional regulation of student athletes was 90 subjects with a percentage of 42% in the high category and the grit aspect as many as 89 subjects with a percentage of 43% in the medium category.